Introduction - Necia Chronister; Lutz Koepnick (Studies in 20th & 21st Century Literature, 2016)
The task of this special issue is to unearth the often denied logic of neoliberal rationality in Germany over the last few decades by exploring how various literary texts, films, and artistic projects, at the level of both content and formal experimentation, have sought to visualize the ramifications of deregulation and ceaseless self-management. The volume features scholarly work on various literary texts, performances, films, time-based art works, and theoretical interventions that explore the nexus between neoliberalism, new media culture, and the landscapes of temporal experience.
Keywords: neoliberalism; 24/7; Jonathan Crary; Wendy Brown; time; German literature; contemporary German film; German performance art